Physical activity level among male and female middle to high school students and impact of perceived school climate: a longitudinal analysis - Tiwari, Biplav Babu; Matta, Jacob; Thomsen, Michael R.; Da, Linlin; Thapa, Kiran; Shen, Ye; Ingels, Justin B.; Rajbhandari-Thapa, Janani (Frontiers in Public Health, 2025)
BackgroundPhysical activity levels are declining among middle and high school students, and schools could provide an ideal space for engaging adolescents in physical activity. The study aimed to assess physical activity levels among male and female middle to high school students and the impact of perceived school climate.MethodsThis longitudinal study utilized the Georgia Student Health Survey (GSHS) from 2016 to 2020, with change in the proportion of physically active students as an outcome and school climate measures as predictors. Factor analysis yielded a composite index for each school climate measure. Descriptive analysis measured the trend and male vs. female differences in physical activity. A multivariable linear regression model was developed to assess the impact of school climate on physical activity and male–female differences.ResultsThe decline in physical activity with increasing grade levels was notably more pronounced in females than males. Improvement in the perception of school climate measures was consistently linked to an increased proportion of physically active students as they progressed to higher grades (for example, change in perception of school connectedness: β = 5.39; p < 0.001).ConclusionThe study findings underscore the importance of fostering positive school climates to mitigate the decline in physical activity levels, especially among adolescent females.